Spatial Variations in Tap Water Isotopes Across Canada: Tracing Water from Precipitation to Distribution and Assess Regional Water Resources - Bhuiyan, Shelina Akter (Université d'Ottawa / University of Ottawa, 2022)
Tap water supply is an essential resource for human societies. However with increasing water use and global warming, this resource needs to be monitored and managed sustainably. Here we use stable isotopes to identify potential issues associated with tap water resources in Canada. We analyze isotopes of 576 tap water samples collected from across Canada and classified them based on their supply sources including groundwater (TapGroundwater), river (TapRiver) and lake (TapLake). We found, isotopic values in tap water correlate strongly with those predicted in local precipitation across Canada, suggesting precipitation is the parent source of tap water. However, this correlation is stronger for TapGroundwater and TapRiver than TapLake. To explain this difference, we constructed a series of water balance models to predict isotopic values of surface water across Canada validated against Canadian rivers isotopes data. We then compared the tap water isotopic values to those predicted in local surface water, which improved the predictability of TapRiver and TapLake but not TapGroundwater. We suggest, TapGroundwater usually reflects isotopic values of annually averaged precipitation whereas TapRiver and TapLake reflect post-precipitation processes. We used the residuals between our observed and predicted isotope data to assess regional sources and processes influencing tap water isotopes across Canada. Regionally, snow/glacier melt from the Rockies contributes to groundwater recharge across Western Canada as well as to some rivers and lakes in Alberta and British Columbia. Also, tap water are highly evaporated across Western Canada irrespective of their sources. Across the Great Lakes and East Coast regions, lakes undergo high evaporative losses. Also, many localities in the East Coast pump and store groundwater in small lakes or ponds exposing them to evaporation. Our data and models provide a baseline for isotope monitoring of tap water resources and isotope forensic studies across Canada.
Keywords: tap water; isotopes; water issues